KANDUNGAN GIZI FORMULA ENTERAL BERBASIS UBI UNGU, IKAN LELE, TEMPE KEDELAI, LABU KUNING - putri, widya ayu kurnia; Zaki, Ibnu; Ramadhan, Gumintang Ratna (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
One of the efforts to manage malnutrition is to fulfill nutritional needs. Fulfillment of nutritional needs can be done through the administration of enteral formulas. The high cost of commercial formulas led to budget swelling in hospitals. Therefore, it is necessary to develop enteral formulas that are cheaper but in accordance with the needs of poor nutrition. One of the development efforts is to utilize local food. Various local foods such as purple sweet potato, catfish, soybean tempe and pumpkin have nutritional content that has the potential as a therapy for malnutrition. This study aims to analyze nutrients including carbohydrates, fats, proteins and -carotene contained in enteral formulas based on purple sweet potato, catfish, soybean tempeh and pumpkin. An experimental study with a completely randomized design (CRD) using four formulas, namely L1, L2, L3 and L4 with a ratio of catfish meal and soybean tempeh flour sequentially 19: 31, 21: 29, 23: 27, 25: 25. Statistical analysis was carried out. with the Oneway Anova test and further tests using the Duncan test. The results showed that in 100g L1 formula contains 73.09% carbohydrates, 8.89% protein and 18.03% fat from total energy and 7.62 mg -carotene. 100g L2 formula contains 74.27% carbohydrates, 9.46% protein and 16.27% fat from total energy as well as 7.40mg -carotene. 100g L3 formula contains 74.29% carbohydrates, 9.78% protein and 15.93% fat from total energy and 10.15 mg -carotene. 100g L4 formula contains 73.62% carbohydrates, 10.21% protein and 16.17% fat from total energy and 9.08 mg -carotene. The formulation with the most nutritional content that meets the needs is the L4 formula. The average nutritional value of enteral L4 formula is 399.60 kcal/100g energy, 10.21% protein, 16.17% fat and 9.08 mg/100g -carotene.